Adsorption of As(Iii) and As(V) Compounds on Fe3o4(0 0 1 Surfaces: A First Principle Study - Baltazar-Rojas, S (Elsevier B.V., 2017)
The adsorption of arsenic species on magnetite has been studied by first principles calculations. From the considered anionic species, a higher adsorption energy was found for the complexation of Fe3O4(0 0 1) with As(III) being 1.3 eV higher than the adsorption energy for As(V). In the case of As(III), a large partial band charge density was found, which was associated to the O[sbnd]Fe bond formation, while more delocalized electron density was found in the adsorption of As(V) subspecies, with the formation of two Fe[sbnd]O bonds. A comparison with sorption of neutral arsenic atoms and O2 molecule was also considered. As(V) is mainly adsorbed on the surface with a double O[sbnd]Fe bond formation, similar to the case of O2 in the most stable configuration. © 2016 Elsevier B.V.